EFFECT OF CAPITAL MARKET DEVELOPMENT ON ECONOMIC GROWTH IN GHANA - Acquah-Sam, Emmanuel; Salami, King (European Scientific Journal, ESJ, 2014)
This study contributes to the general body of knowledge and research works in the area of the role of finance in economic growth and development with specific reference to the effect of capital market development on economic growth in Ghana. This study was motivated by the fact that some studies have reported negative effects of capital markets on economic growth in some developing nations, despite its expected positive effect on growth and development. The study is a multiple linear regression based on quarterly time series data spanning from 1991:1 to 2011:4. Exploratory data analysis was used to ensure that the basic assumptions of regression analysis were verified and resolved. Structural Equation Modeling (SEM) through Path Analysis (i.e. Layered Regression Technique) was used to identify the possible causal relationship between GDP growth and capital market development, as well as other causal effects in the model. The study shows that GDP growth is linearly related to by the independent variables in the model. There is also a positive bi-directional relationship between economic growth and capital market development. However, the stronger effect is from capital market development to economic growth. The study recommends that developing countries should place greater emphasis on financial sector development with specific focus on capital markets development to promote economic growth.